Stability Study of Nanoparticle, Microemulsion, Multiple Emulsion and Niosome Cream From Ethyl Acetat Fraction Of EGCG in Green Tea (Camelia sinensis L.) Leaf - widyaningrum, naniek; Taufiq, Hudan; Lestari, Sri; Devitasari B, Andi Nur; Farahiya, Binta; Fairuzia, Intan; Arief, Thendi Abdul (International Pharmacy Acta, 2024)
The stability of EGCG in green tea leaves is significantly impacted by temperature and storage duration. The formulation of w/o cream was not the best for preserving the stability of EGCG, thus it was required to change the way cosmetic preparations were delivered in a number of dosage forms. Physical and chemical tests were conducted on the ethyl acetate fraction of green tea leaves (Camellia sinensis L.) in the dosage forms of nanoparticles, microparticles, multiple emulsions, and niosomes cream. Test of accelerated stability (temperature 50, 60, and 7000C). HPLC was used to evaluate EGCG. The results of the physical test preparations for nanoparticles, microemulsions, multiple emulsions and niosomes met the positive control parameters, namely the dispersion power of 6.34 ± 0.76 cm; 5.26 ± 0.45 cm; 6.07 ± 0.76 cm; 6.16 ± 0.19 cm. pH of each preparation 4.73 ± 0.10; 5.30 ± 0.2; 5.46 ± 0.19; 5.05 ± 0 and viscosity 2834 ± 844.6744; 3390 ± 1.57; 2582 ± 360; 3300 ± 173.20. EGCG levels in cream preparations of nanoparticles, microparticles, multiple emulsions, and niosomes at a temperature of 250C and 100C, respectively 476.0236 ± 332.6097; 32.6651 ± 3.5385; 0.2221 ± 0.0078; 3.4320 ± 1.9533. In contrast to W/O creams, preparations including nanoparticles, microemulsions, multiple emulsions, and niosomes can preserve their physical and chemical stability. Nanoparticle cream, microemulsion, multiple emulsion type W/O/W, and niosomes were proven to maintain physical stability compared to cream type O/W. Nanoparticle cream, microemulsion, multiple emulsion type W/O/W, and niosomes were proven to maintain chemical stability compared to cream type O/W.